Latynizmy w powieściach bałkańskich Teodora Tomasza Jeża - Żuraszek-Ryś, Iwona (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2024)
The considerations presented in the article were inspired by Professor Walczak’s remarks about T.T. Jeż’s overuse of Latinisms. The conducted research confirms this thesis also in relation to the Balkan novels – an analysis of their lexis showed that one of the most numerous groups of foreign vocabulary items contained in them are words of Latin origin. Their significant number was dictated by, among others, their subject matter, the genre of the texts or the artistic considerations. In addition, it should not be forgotten that the Polish language was and still is significantly saturated with Latinisms. The vocabulary originating from the Roman cultural circle which was recorded in the examined material included words and acquired phrases as well as quotations and even word-formation particles. Jeż not only used a specific set of Latinisms, but also modified them by introducing new words.